Government governance, executive networks and enterprise R&D expenditure - Xin Jin; Guangyong Lei; Junli Yu (China Journal of Accounting Research, 2016)
The increasingly competitive market environment makes independent innovation the core of the enterprise's and evens the country's competitiveness. In order to solve the problem of its own limited R&D resources, firms need to find access to outside resources. Since the government mainly provides policy and financial support, the information diffusion and learning effects of executive networks can effectively compensate for the shortage of formal institutional arrangements. In view of this, we manually collect data on R&D expenditures and executive networks having common management members in China A-share listed companies from 2007 to 2010. Combined with corporate governance and government governance data, this paper empirically tests the influence of government governance and executive networks on enterprise innovation. The empirical results reveal that the governance efficiency of the government where the enterprise is located determines the efficiency of resource allocation firms are faced with, which provides institutional constraints on corporate R&D intensity, and that the establishment and scale of executive networks do contribute to R&D decisions. Further testing shows that compared with non-state-owned enterprises, state-owned enterprises are faced with relatively weaker restraints and pressures in terms of policy, finance, technology and competition. Thus, they show no obvious reliance on government governance quality and the information diffusion of executive networks. The findings of this study help us to understand the role of informal systems in social economics, such as relationship networks and social capital, in the context of China's economic development, and provide relevant evidence and enrich macro and micro studies of "government and market" and "market and enterprise" relationships.
Keywords: G39; M41; 650; Government governance; Executive networks; R&D investment; State-owned enterprises